The Influence of Emotional Intelligence and Entrepreneurship Learning Achievement (PKK) on Entrepreneurial Interest in Class XI Students of SMKN 1 Banyudono Academic Year 2023/2024 - Desi Fitriana; Susantiningrum (Jurnal Ilmiah Pendidikan Holistik (JIPH), 2024)
This research is a quantitative descriptive type that tracks the influence of entrepreneurial learning achievement (Creative and Entrepreneurship Projects) and emotional intelligence on students' interest in entrepreneurship in class XI of SMKN 1 Banyudono for the 2023/2024 academic year. The study's findings indicate that: (1) emotional intelligence positively and significantly influences class 31,562 > 1,972; (2) entrepreneurial learning achievement (PKK) positively and significantly influences class tcount > ttable value (2.564 > 1.972); and (3) there is a positive and significant relationship between emotional intelligence and PHK on class tcount > ttable value (2.564 > 1.972) and students' interest in entrepreneurship at SMKN 1 Banyudono, as demonstrated by the calculated f value, which displays a value of 974.418 (dfl = 2, df2 = 188, α = 0.05) with table = 3.045. In this study, the regression model is Y=42.34+0.784X+0.205X2.